UJI KEANDALAN MODEL SACRAMENTO PADA DAS BEDADUNG DAN DAS KLOPOSAWIT - Sri Wahyuningsih; Elida Novita; . Indarto (JURNAL AGROTEKNOLOGI, 2010)
Sacramento model is once of rainfall runoff Library (RRL) model which used to measure the flow components that include rainfall, evaporation and discharge. Sacramento model using soil moisture measurements to simulate the water balance at the catchment area. Sacramento model is a relatively new model so needs to be done the testing of this model. The testing process is often used for modeling is a process of calibration and validation. Aim this study is to evaluate the feasibility of the Sacramento model to be applied in the Bedadung and Kloposawit watershed and compare the optimal parameters the both watersheds on the basis of their characteristics. The methodology used is the calibration and validation. Calibration is done by automatic methods (generic) and the method of trial and error (manually) while the method for validating is simple-sample test. The results showed that the Sacramento model proper to applied in the Bedadung and Kloposawit watershed. This is indicated by the Nash coefficient, the coefficient of correlation and bias. By using generic methods on Bedadung watershed available the Nash coefficient value of 0.849, the correlation coefficient for 0.993 and bias of 8.11. Meanwhile, if using manual methods will be obtained the Nash coefficient for 0.906 and correlation coefficient equal to 0.997. While the generic calibration method in the Kloposawit watershed available the Nash coefficient values obtained for 0,894, the correlation coefficient for 0.967 and bias of 11.11. Meanwhile, if using manual methods will be obtained for Nash coefficient is 0.918 and correlation coefficient equal to 0968. The method of validation model with a simple -sample test. The result of validation for Klopo sawit watershed is the Nash coefficient value of 0.913 and the correlation coefficient for 0.989. While the Bedadung watershed is the Nash coefficient value of 0.860, the correlation coefficient for 0.991.Keywords: sacramento, calibration, validation, simple-sample test, nash coefficient